Sodium-ion battery positive electrode slurry, preparation method and application thereof, positive plate and sodium-ion battery
By using crosslinked sodium polyacrylate with a neutralization degree of 50% to 90% in the positive electrode slurry of sodium ion battery, the problem of gelation phenomenon of the positive electrode material during homogenization is solved, and the energy density and circulation of the battery are improved. performance.
Patent Information
- Application Number
- CN202411637056.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
The positive electrode material of sodium ion battery is prone to gel during homogenization, resulting in a significant increase in viscosity and affecting the electrochemical performance of the battery, such as energy density.
The positive electrode slurry of sodium ion battery including positive electrode active materials, conductive agents, binders, crosslinked sodium polyacrylate and organic solvents are used. The neutralization degree of crosslinked sodium polyacrylate is 50%~90%, and its carboxylic acid is The group can neutralize the residual base of the cathode active material and absorb and fix trace amounts of water generated by the acid and base neutralization.
It effectively inhibits the slurry gel caused by the high alkali system, improves the stability of the slurry, avoids moisture residue, and enhances the energy density and circulation performance of sodium ion batteries.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery positive electrode slurry and a preparation method, application, positive electrode sheet and sodium ion battery. Background Art
[0002] In recent years, with the rapid growth of the market size of new energy vehicles and electrochemical energy storage industries, secondary batteries have been widely used. Sodium-ion batteries and lithium-ion batteries are both "rocking chair batteries" of ion migration, and their structures and working principles are similar. Compared with lithium-ion batteries, sodium-ion batteries have lower manufacturing costs. The main reasons include: (1) The proportion of sodium in the earth's crust reaches 2.75% (mass fraction), which is more than 400 times that of lithium, and is widely distributed; (2) Due to the excellent interfacial desolvation ability of sodium ions, sodium-ion batteries can achieve the required ionic conductivity of the battery with a lower concentration of electrolyte compared to lithium-ion batteries; (3) Sodium ions do not react with aluminum, and sodium-ion batteries can use cheap aluminum foil as the negative electrode collector. In addition, compared with lithium-ion batteries, sodium-ion batteries have obvious advantages in safety and low-temperature performance. Therefore, sodium-ion batteries are expected to be widely used in short-term energy storage, power generation side energy storage, electric two-wheeled vehicles, A0 / A00 electric vehicles and other fields in the future.
[0003] The main structure of sodium-ion batteries includes positive electrode sheets, negative electrode sheets, electrolytes and separators. Among them, the positive electrode sheets have an important impact on key indicators such as battery energy density, cycle life and safety, and are mainly composed of positive electrode active materials, conductive agents and binders. However, during the homogenization process of positive electrode materials for sodium-ion batteries, the viscosity of the positive electrode slurry will increase significantly or even gel after a short period of standing (about 2 hours), causing subsequent coating thickness fluctuations or inability to coat, which in turn affects the electrochemical properties of sodium-ion batteries such as battery energy density. Summary of the invention
[0004] Based on this, some embodiments of the present application provide a sodium ion battery positive electrode slurry, which is beneficial to improve its gel phenomenon and enhance the electrochemical performance of the sodium ion battery, such as energy density.
[0005] In addition, other embodiments of the present application also provide a method for preparing a positive electrode slurry for a sodium ion battery, an application, a positive electrode sheet and a sodium ion battery.
[0006] A positive electrode slurry for a sodium ion battery, comprising: a positive electrode active material, a conductive agent, a binder, cross-linked sodium polyacrylate and an organic solvent;
[0007] Wherein, the neutralization degree of the cross-linked sodium polyacrylate is 50% to 90%.
[0008] In some of the embodiments, the neutralization degree of the cross-linked sodium polyacrylate is 55% to 75%.
[0009] In some of the embodiments, the average particle size of the cross-linked sodium polyacrylate is 10 μm to 400 μm, and optionally, the average particle size is 50 μm to 200 μm.
[0010] In some of the embodiments, the raw materials of the sodium ion battery positive electrode slurry include, by weight: 45 to 65 parts of positive electrode active material, 0.5 to 2.5 parts of conductive agent, 1.2 to 3.5 parts of binder, 0.5 to 4.5 parts of cross-linked sodium polyacrylate and 20 to 45 parts of organic solvent.
[0011] In some embodiments, the positive electrode active material includes one or a combination of layered transition metal oxides, Prussian blue-based positive electrode materials, and polyanion compounds.
[0012] In some embodiments, the binder includes one or a combination of polyvinylidene fluoride, polyacrylic acid and polytetrafluoroethylene.
[0013] In some embodiments, the binder includes polyvinylidene fluoride.
[0014] In some embodiments, the conductive agent includes one or a combination of carbon nanotubes, conductive carbon black and graphene.
[0015] In some embodiments, the solvent includes one or a combination of N-methylpyrrolidone and N,N-dimethylformamide.
[0016] In some embodiments, the raw materials for preparing the cross-linked sodium polyacrylate include: acrylic acid, a cross-linking agent, a neutralizing agent and an initiator;
[0017] Wherein, the crosslinking agent includes one or more of N,N-methylenebisacrylamide, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diacrylate, polyethylene glycol diglycidyl ether, ethoxylated glycerol triacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, allyl methacrylate, triallylamine, tetraallyl ammonium chloride, tetraallyloxyethane, pentaerythritol triacrylate, pentaerythritol triallyl ether, trimethylolpropane triacrylate and ethoxylated trimethylolpropane triacrylate;
[0018] The neutralizing agent includes one or more of alkali metal hydroxides, alkali metal oxides, alkali metal carbonates, alkali metal bicarbonates and ammonium salts. Optionally, the neutralizing agent includes one or more of sodium hydroxide, sodium carbonate and sodium bicarbonate.
[0019] The initiator includes one or more of an oxidant, a reducing agent and a photoinitiator;
[0020] The oxidant includes one or more of hydrogen peroxide, sodium persulfate, potassium persulfate, ammonium persulfate, tert-butyl hydroperoxide, di-tert-butyl peroxide and azo compounds. Optionally, the oxidant includes one or more of azobisisobutyronitrile, azobisdimethylvaleronitrile, 2,2-azobis(2-amidinopropane) dihydrochloride, azobisamidinopropane dihydrochloride, 2,2-azobis(N,N-dimethyleneisobutyramidine) dihydrochloride, 2-(carbamoylazo)isobutyronitrile and 4,4'-azobis(4-cyanovaleric acid);
[0021] The reducing agent includes one or more of ascorbic acid, ammonium bisulfite, sodium sulfite, sodium bisulfite, sodium pyrosulfite, sodium thiosulfate, ammonium thiosulfate, ammonium dithionite, ammonium sulfide, alkali metal bisulfite, alkali metal sulfate, alkali metal thiosulfate, alkali metal dithionite and alkali metal sulfide; optionally, the reducing agent includes one or more of ascorbic acid, sodium sulfite and sodium pyrosulfite;
[0022] The photoinitiator includes one or more of benzophenone, benzoin ether, dialkyl acetophenone, hydroxyalkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and α-amino ketone.
[0023] A method for preparing a sodium ion battery slurry comprises the following steps:
[0024] The positive electrode active material, the conductive agent, the binder, the cross-linked sodium polyacrylate and the organic solvent are mixed and stirred, and then filtered to prepare a positive electrode slurry for a sodium ion battery;
[0025] Wherein, the neutralization degree of the cross-linked sodium polyacrylate is 50% to 90%.
[0026] In some embodiments, the step of mixing the positive electrode active material, the conductive agent, the binder, the cross-linked sodium polyacrylate and the organic solvent comprises:
[0027] Stirring and mixing the positive electrode active material, the conductive agent, the binder and the cross-linked sodium polyacrylate for the first time;
[0028] The organic solvent is added to the obtained mixture, and stirring and mixing are performed for a second time.
[0029] The invention discloses an application of cross-linked sodium polyacrylate in preparing positive electrode slurry for sodium ion batteries, wherein the neutralization degree of the cross-linked sodium polyacrylate is 50% to 90%.
[0030] In some of the embodiments, the neutralization degree of the cross-linked sodium polyacrylate is 55% to 75%.
[0031] In some of the embodiments, the average particle size of the cross-linked sodium polyacrylate is 10 μm to 400 μm.
[0032] In some of the embodiments, the average particle size of the cross-linked sodium polyacrylate is 50 μm to 200 μm.
[0033] A positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer arranged on at least one side surface of the positive electrode current collector, wherein the positive electrode active layer is prepared by the above-mentioned positive electrode slurry for a sodium ion battery.
[0034] A sodium ion battery comprises a positive electrode sheet, a negative electrode sheet and a separator spaced between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is as described above.
[0035] Compared with the positive active materials of lithium-ion batteries, the positive active materials of sodium-ion batteries have higher residual alkali. During the positive electrode homogenization process, excessive alkalinity will destroy the CF / CH bond in the binder, such as polyvinylidene fluoride, resulting in a significant increase in the viscosity of the positive electrode slurry after a short period of standing (about 2 hours) after homogenization, or even gelation, causing subsequent coating thickness fluctuations or inability to coat, thereby affecting the electrochemical performance of the sodium-ion battery. The traditional method neutralizes the residual alkali by adding inhibitors such as oxalic acid, but water will be produced at the same time, which will have an adverse effect on the battery performance. Based on this, some embodiments of the present application provide a positive electrode slurry for a sodium-ion battery, including a positive electrode active material, a conductive agent, a binder, a cross-linked sodium polyacrylate with a certain degree of neutralization, and an organic solvent. The carboxylic acid group contained in the cross-linked sodium polyacrylate can effectively neutralize the residual alkali of the sodium ion positive electrode active material, thereby inhibiting the slurry gel caused by the high alkaline system. At the same time, the trace water produced by the acid-base neutralization can be absorbed and fixed in the cross-linked sodium polyacrylate, thereby improving the stability of the slurry. The volume of the cross-linked sodium polyacrylate increases after absorbing water, and it can be removed by a filter screen later. Therefore, the above-mentioned sodium ion battery positive electrode slurry not only neutralizes the residual alkali and absorbs moisture, but the cross-linked sodium polyacrylate remaining in the slurry can also play a role in sodium supplementation, which helps to improve the energy density of the sodium ion battery. DETAILED DESCRIPTION
[0036] In order to facilitate the understanding of the present application, the present application will be described more comprehensively below in conjunction with the specific embodiments. The preferred embodiments of the present application are provided in the specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0038] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:
[0039] In this application, "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features.
[0040] In the description of the present application, “plurality” means at least two, for example, two, three, etc., unless otherwise clearly and specifically defined.
[0041] In this application, "one or several" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0042] In this application, the percentage concentration involved, unless otherwise specified, refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.
[0043] In this document, "further", "further", "particularly", "for example", "such as", "example", "for example", etc. are used for descriptive purposes, indicating that the previous and subsequent technical solutions are related in terms of the content covered, but should not be understood as a limitation on the previous technical solution, nor can it be understood as a limitation on the protection scope of this document. In this document, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0044] Herein, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If multiple "optional" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" item is independent of each other. In this application, descriptions such as "optionally contain", "optionally include", etc. mean "contain or not contain". "Optional component X" means that component X exists or does not exist, or means that component X is contained or not contained.
[0045] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.
[0046] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0047] The terms "including" and "having" and any variations thereof in the embodiments of the present application are intended to cover non-exclusive inclusions. For example, a process, method, system, product, or device that includes a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units that are not listed, or may optionally include other steps or components that are inherent to these processes, methods, products, or devices.
[0048] Reference to "embodiments" in this application means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application may be combined with other embodiments.
[0049] Traditional technology discloses a method of using oxalic acid, malic acid, etc. as inhibitors to neutralize the residual alkali of the positive electrode active material, which can reduce gel to a certain extent. However, acid-base neutralization will produce trace amounts of water. The positive electrode active material of the sodium ion battery has strong hygroscopicity, and contact with water will generate NaOH. The uneven material surface may have an adverse effect on the electrochemical properties of the electrode, causing damage to the battery cell. In addition, oxalic acid is highly toxic and corrosive, and there is a risk of use. Another traditional technology uses oxalic acid as an inhibitor and introduces composite hydrophobic particles, including at least one of silica, diatomaceous earth and montmorillonite, to reduce the hygroscopicity of the positive electrode slurry. However, this solution will introduce more silicon impurities, resulting in a decrease in the energy density, cycle performance and other performance of the sodium ion battery. In addition, there is a traditional technology that uses organic acid as an alkaline inhibitor, and one or more of aluminum isopropoxide, tetrabutyl titanate, zirconium n-butoxide and tetraethyl silicate as a dehydrating agent to coat a layer of oxide on the surface of the positive electrode active material to reduce the hygroscopic properties of the surface of the positive electrode active material. This method may have an adverse effect on the electron migration of the positive electrode active material, and the selected dehydrating agent is a hazardous chemical with a large chemical reaction activity and the risk of causing combustion and explosion, which is not conducive to use in production.
[0050] In order to solve the above technical problems, the present application proposes a sodium ion battery positive electrode slurry and a preparation method thereof, which can improve the gel of the sodium ion battery positive electrode slurry, reduce the moisture in the slurry, and at the same time make up for the Na consumed by the negative electrode material to form the SEI film. + , which helps to improve the energy density of sodium-ion batteries.
[0051] Specifically, the first aspect of the present application provides a positive electrode slurry for a sodium ion battery, comprising: a positive electrode active material, a conductive agent, a binder, a cross-linked sodium polyacrylate and an organic solvent;
[0052] Among them, the neutralization degree of cross-linked sodium polyacrylate is 50%~90%.
[0053] The above-mentioned positive electrode slurry of the sodium ion battery includes positive electrode active materials, conductive agents, binders, cross-linked sodium polyacrylate with a certain degree of neutralization, and organic solvents. The carboxylic acid groups contained in the cross-linked sodium polyacrylate can effectively neutralize the residual alkali of the sodium ion positive electrode active materials, thereby inhibiting the slurry gel caused by the high alkali system. At the same time, the trace water produced by the acid-base neutralization can be absorbed and fixed in the cross-linked sodium polyacrylate, thereby improving the stability of the slurry. The volume of the cross-linked sodium polyacrylate increases after absorbing water, and can be removed through a filter screen later. Therefore, the above-mentioned sodium ion battery slurry not only neutralizes the residual alkali and absorbs water, but the cross-linked sodium polyacrylate remaining in the slurry can also play a role in sodium supplementation, which helps to improve the energy density of the sodium ion battery.
[0054] In addition, the conventional method improves hygroscopicity by introducing composite hydrophobic particles, including at least one of silicon dioxide, diatomaceous earth and montmorillonite. However, this solution introduces more silicon impurities, resulting in a decrease in the energy density and cycle performance of the sodium ion battery. In some embodiments of the present application, the elements contained in the cross-linked sodium polyacrylate are all contained in the positive electrode slurry itself, and no impurity elements are introduced into the sodium ion battery slurry, which will not cause a decrease in the energy density and cycle performance of the sodium ion battery. On the contrary, the remaining cross-linked sodium polyacrylate can also play a role in supplementing sodium, which helps to improve the energy density of the sodium ion battery.
[0055] Neutralization degree refers to the degree of neutralization reaction, usually expressed as the ratio of the amount of substance of the two products. For example, when preparing a sodium acrylate solution with a neutralization degree of 70%, it means that the degree of neutralization of acrylic acid by sodium hydroxide is 70%.
[0056] In one example, the neutralization degree of cross-linked sodium polyacrylate can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or a range consisting of any two of these values, but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The neutralization degree of cross-linked sodium polyacrylate is greater than 90%, and the carboxylic acid groups are not dense enough. It is difficult to fully neutralize with the residual alkali of the sodium ion positive electrode active material during the homogenization process to inhibit the slurry gel caused by the high alkali system. In addition, too high a neutralization degree will increase the charge density on the molecular chain and enhance the electrostatic repulsion between the molecular chains, causing the three-dimensional network structure of the gel to become loose, which is easy to deform and break after absorbing water, and has poor water retention. The neutralization degree of cross-linked sodium polyacrylate is less than 50%. Due to the low water absorption rate and slow water absorption rate caused by too few carboxylate groups, the trace water generated by acid-base neutralization is difficult to be fixed by the cross-linked sodium polyacrylate and removed by filtration, and remains in the positive electrode slurry, affecting the battery performance. In some embodiments of the present application, by selecting a neutralization degree of 50% to 90% for the cross-linked sodium polyacrylate, it is beneficial to neutralize the residual alkali of the sodium ion positive electrode active material to inhibit the slurry gel caused by the high alkali system. At the same time, the water generated by the acid-base neutralization can be fixed in the network structure of the cross-linked sodium polyacrylate and subsequently removed by filtration.
[0057] In some embodiments, the degree of neutralization of the cross-linked sodium polyacrylate is 55% to 75%. Optionally, the degree of neutralization of the cross-linked sodium polyacrylate is 55% to 65%. For example, the degree of neutralization of the cross-linked sodium polyacrylate is 60%.
[0058] In some embodiments, the average particle size of the cross-linked sodium polyacrylate is 10 μm to 400 μm. For example, the average particle size of the cross-linked sodium polyacrylate can be, but is not limited to, 10 μm, 50 μm, 80 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, or a range consisting of any two of these values. Optionally, the average particle size of the cross-linked sodium polyacrylate is 50 μm to 200 μm.
[0059] Cross-linked sodium polyacrylate is a highly absorbent resin (SAP) with a three-dimensional network structure and water-absorbing groups, which can absorb water tens to thousands of times its own weight. For example, the water absorption rate of cross-linked sodium polyacrylate is greater than or equal to 10g / g, or the water absorption rate is greater than or equal to 50g / g, or the water absorption rate is greater than or equal to 100g / g. The water absorption rate refers to the ratio of the amount of liquid absorbed by a substance in a certain period of time to the weight of the substance itself. In one example, the water absorption rate of cross-linked sodium polyacrylate is greater than or equal to 50g / g.
[0060] In the present application, cross-linked sodium polyacrylate can be prepared by a method commonly used in the art, and only needs to satisfy the neutralization degree of 50% to 90%. For example, cross-linked sodium polyacrylate with a neutralization degree of 50% to 90% can be directly commercially available.
[0061] In some of the embodiments, the raw materials for preparing the cross-linked sodium polyacrylate include: acrylic acid, a cross-linking agent, a neutralizing agent, an initiator, and the like.
[0062] Specifically, the crosslinking agent is a compound having two or more polymerizable groups that can be free radically polymerized into a polymer network. Optionally, the crosslinking agent includes one or more of N,N-methylenebisacrylamide, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diacrylate, polyethylene glycol diglycidyl ether, ethoxylated glycerol triacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, allyl methacrylate, triallylamine, tetraallyl ammonium chloride, tetraallyloxyethane, pentaerythritol triacrylate, pentaerythritol triallyl ether, trimethylolpropane triacrylate, and ethoxylated trimethylolpropane triacrylate. In one embodiment, the crosslinking agent includes polyethylene glycol diacrylate (PEGDA) and ethoxylated trimethylolpropane triacrylate crosslinker (TMP(EO)15TA).
[0063] Specifically, the neutralizing agent includes one or more of alkali metal hydroxides, alkali metal oxides, alkali metal carbonates, alkali metal bicarbonates and ammonium salts. Optionally, the alkali metal is sodium and / or potassium. In one embodiment, the neutralizing agent includes one or more of sodium hydroxide, sodium carbonate and sodium bicarbonate. In one example, the neutralizing agent includes sodium hydroxide. The amount of the neutralizing agent can be adjusted according to the value of the neutralization degree.
[0064] Specifically, the initiator includes one or more of an oxidizing agent, a reducing agent and a photoinitiator.
[0065] Optionally, the oxidant includes one or more of hydrogen peroxide, sodium persulfate, potassium persulfate, ammonium persulfate, tert-butyl hydroperoxide, di-tert-butyl peroxide and azo compounds. For example, the oxidant includes an azo compound. Further, the oxidant includes one or more of azobisisobutyronitrile, azobisdimethylvaleronitrile, 2,2-azobis(2-amidinopropane) dihydrochloride, azobisamidinopropane dihydrochloride, 2,2-azobis(N,N-dimethyleneisobutyramidine) dihydrochloride, 2-(carbamoylazo)isobutyronitrile and 4,4'-azobis(4-cyanovaleric acid).
[0066] Optionally, the reducing agent includes one or more of ascorbic acid, ammonium bisulfite, sodium sulfite, sodium bisulfite, sodium pyrosulfite, sodium thiosulfate, ammonium thiosulfate, ammonium dithionite, ammonium sulfide, alkali metal bisulfite, alkali metal sulfate, alkali metal thiosulfate, alkali metal dithionite and alkali metal sulfide. Further, the reducing agent includes one or more of ascorbic acid, sodium sulfite and sodium pyrosulfite.
[0067] Optionally, the photoinitiator includes one or more of benzophenone, benzoin ether, dialkyl acetophenone, hydroxyalkyl ketone (such as 1-hydroxycyclohexyl phenyl ketone), phenyl glyoxylate, benzyl dimethyl ketal (such as 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone), diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and α-amino ketone.
[0068] In one example, the initiator includes a photoinitiator, an oxidant, and a reducing agent. For example, the photoinitiator may be, but is not limited to, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide (IRGACURE 819), the oxidant may be, but is not limited to, sodium persulfate, and the reducing agent may be, but is not limited to, sodium pyrosulfite.
[0069] It is understandable that commonly used additives, such as pentasodium diethylenetriaminepentaacetate (EDTA(5Na)), sodium dodecyl sulfate, etc., may also be added during the preparation of the cross-linked sodium polyacrylate.
[0070] In one embodiment, the preparation steps of cross-linked sodium polyacrylate include:
[0071] In a 5L glass reactor, add 1127g of 32% sodium hydroxide solution and 1273g of deionized water, slowly add 1300g of acrylic acid under stirring, and cool to 20°C with cooling water. Then add 1.2g of polyethylene glycol diacrylate (PEGDA, molecular weight 508), 4.2g of ethoxylated trimethylolpropane triacrylate crosslinker (TMP(EO)15TA), 5.0g of 1% diethylenetriamine pentaacetic acid pentasodium (EDTA(5Na)) aqueous solution and 21.6g of 1% sodium dodecyl sulfate aqueous solution, and mix well. Then add 26g of 1% diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide (IRGACURE 819) acrylic acid solution, 10.4g of 5% sodium persulfate aqueous solution and 13g of 1% sodium pyrosulfite aqueous solution. The obtained solution was mixed evenly and poured into a rectangular polymerization tank, and then placed in a UV irradiation device at a light intensity of 5mw / cm 2 The polymerization is initiated under the light conditions, and the polymerization reaction occurs in about 30 seconds, and foaming and gel production are produced at the same time, and the aging is continued for 5 minutes. Then the polymerized colloid is taken out, and the colloid is continuously added into the screw crushing granulator for gel granulation to obtain a 4mm×4mm gel block absorbent polymer lipid, which is then dried in a blast oven at 150℃ for 1h. The above dried particles are crushed by a pulverizer and classified by a sieve to obtain a cross-linked sodium polyacrylate with a neutralization degree of 50% and an average particle size of 50μm~100μm.
[0072] It can be understood that the above only provides a more specific preparation method of cross-linked sodium polyacrylate, but is not limited thereto, and it is sufficient to obtain cross-linked sodium polyacrylate with a neutralization degree of 50% to 90%.
[0073] The positive electrode active material can be a common sodium ion battery positive electrode active material in the art, and is not particularly limited here. For example, the positive electrode active material of the sodium ion battery includes one or a combination of layered transition metal oxides, Prussian blue positive electrode materials, and polyanion compounds. Among them, the layered transition metal oxide is a layered structure material composed of transition metals (such as Fe, Mn, Ni, Co, etc.) and oxygen elements. For example, Na x MO2, wherein M is one or a combination of Fe, Mn, Ni, Co and Cr. In one example, the layered transition metal oxide is, for example, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2. The chemical formula of Prussian blue cathode material is Nax M1[M2(CN)6] y •nH2O, M1 and M2 are transition metal elements, such as Fe, Mn, Cu, Ni, Co, etc. Polyanionic compounds are generally composed of cations and anions. The anions are mainly MO x Polyhedron (x is V, Mn, Fe, Cr, Ti, etc.), (XO4) m n- or (X m O 3m+1 ) n- (x is P, S, Si, As, etc.), where MO x Polyhedron and (XO4) m n- or (X m O 3m+1 ) n- The three-dimensional structure is formed by sharing angles or edges.
[0074] In some embodiments, the binder includes one or a combination of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) and polytetrafluoroethylene (PTEF). In some embodiments, the binder includes PVDF. In a specific example, the PVDF is Solvay 5130.
[0075] In some embodiments, the conductive agent includes a carbon material. Specifically, the conductive agent includes one or a combination of carbon nanotubes, conductive carbon black and graphene. The carbon nanotubes are, for example, single-walled carbon nanotubes.
[0076] In some embodiments, the organic solvent comprises one or a combination of N-methylpyrrolidone and N,N-dimethylformamide. Alternatively, the organic solvent comprises N-methylpyrrolidone.
[0077] In some embodiments, the raw materials of the sodium ion battery positive electrode slurry include, by weight: 45 to 65 parts of sodium ion battery positive electrode active material, 0.5 to 2.5 parts of conductive agent, 1.2 to 3.5 parts of binder, 0.5 to 4.5 parts of cross-linked sodium polyacrylate and 20 to 45 parts of organic solvent.
[0078] For example, in the raw materials of the positive electrode slurry of the sodium ion battery, the mass fraction of the positive electrode active material of the sodium ion battery can be, but not limited to, 45 parts, 46 parts, 48 parts, 50 parts, 52 parts, 55 parts, 56 parts, 58 parts, 60 parts, 62 parts, 65 parts, or a range consisting of any two of these values. The mass fraction of the conductive agent can be, but not limited to, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, or a range consisting of any two of these values. The mass fraction of the binder can be, but not limited to, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, or a range consisting of any two of these values. The mass fraction of cross-linked sodium polyacrylate can be, but is not limited to, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 4, 4.5 or any two of these values. The mass fraction of organic solvent can be, but is not limited to, 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45 or any two of these values.
[0079] In some embodiments, the viscosity of the positive electrode slurry of the sodium ion battery is 6000cp~9000cp. For example, the viscosity of the positive electrode slurry of the sodium ion battery can be, but is not limited to, 6000cp, 6500cp, 7000cp, 7500cp, 8000cp, 8500cp, 9000cp or a range consisting of any two of these values.
[0080] The second aspect of the present application provides a method for preparing a positive electrode slurry for a sodium ion battery, comprising the following steps:
[0081] The positive electrode active material, the conductive agent, the binder, the cross-linked sodium polyacrylate and the organic solvent are mixed and stirred, and then filtered to prepare a positive electrode slurry for a sodium ion battery;
[0082] Wherein, the neutralization degree of the cross-linked sodium polyacrylate is 50% to 90%.
[0083] The specific components are the same as those in the first aspect, and will not be described in detail here.
[0084] In some embodiments, the step of mixing the positive electrode active material, the conductive agent, the binder, the cross-linked sodium polyacrylate and the organic solvent comprises:
[0085] Stirring and mixing the sodium ion battery positive electrode active material, the conductive agent, the binder and the cross-linked sodium polyacrylate for the first time;
[0086] The organic solvent is added to the obtained mixture, and stirring and mixing are performed for a second time.
[0087] The above two-step mixing method is beneficial to improving dispersion uniformity and dispersion efficiency.
[0088] Specifically, the first stirring and mixing time is 30 minutes, and the second stirring and mixing time is 180 minutes.
[0089] Specifically, the rotation speed of the second stirring and mixing is greater than the rotation speed during the first stirring process.
[0090] In some embodiments, during the first stirring and mixing process, the rotational speed is 20 rpm, the rotational speed is 500 rpm, and during the second stirring and mixing process, the rotational speed is 30 rpm, and the rotational speed is 2000 rpm.
[0091] The revolution rate refers to the speed at which the stirring device as a whole rotates around a central axis. The rotation rate refers to the speed at which the stirring components (such as stirring paddles, dispersion discs, etc.) in the stirring device rotate themselves. Usually, the revolution rate is smaller than the rotation rate.
[0092] It can be understood that the above only provides a more specific mixing method, but is not limited thereto, as long as the components can be fully mixed and uniform.
[0093] In some embodiments, in the filtering step, the mesh size of the sieve used is 150-250 meshes. The cross-linked sodium polyacrylate that swells due to water absorption is removed by filtering to prevent water from remaining in the slurry and affecting the battery performance.
[0094] The third aspect of the present application provides an application of a cross-linked sodium polyacrylate in the preparation of a positive electrode slurry for a sodium ion battery;
[0095] Wherein, the neutralization degree of the cross-linked sodium polyacrylate is 50% to 90%.
[0096] The cross-linked sodium polyacrylate has high safety. When used in the positive electrode slurry of sodium ion batteries, the carboxylic acid groups contained in it can effectively neutralize the residual alkali of the sodium ion positive electrode active material, thereby inhibiting the slurry gel caused by the high alkali system. At the same time, the trace water produced by the acid-base neutralization can be absorbed by the cross-linked sodium polyacrylate and fixed by its cross-linked structure, thereby improving the stability of the slurry. After absorbing water, the volume of the cross-linked sodium polyacrylate increases and can be removed by the filter. In addition, when it is used in the positive electrode slurry of sodium ion batteries, no impurity elements are introduced, and it can also play the role of sodium supplementation, which helps to improve the energy density of sodium ion batteries.
[0097] In addition, traditional cross-linked sodium polyacrylate is usually used as a water-absorbing resin in sanitary products such as diapers, sanitary napkins, etc., while in some embodiments of the present application, cross-linked sodium polyacrylate is used in sodium ion batteries, providing a new application of cross-linked sodium polyacrylate.
[0098] The specific cross-linked polypropylene sodium and sodium ion battery positive electrode slurry are the same as those described above and will not be described in detail here.
[0099] The fourth aspect of the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active layer arranged on at least one side surface of the positive electrode current collector, wherein the positive electrode active layer is prepared by the above-mentioned sodium ion battery positive electrode slurry.
[0100] The above-mentioned sodium ion battery positive electrode slurry contains cross-linked sodium polyacrylate, which has high safety. The carboxylic acid groups contained in the cross-linked sodium polyacrylate can effectively neutralize the residual alkali of the sodium ion positive electrode active material, thereby inhibiting the slurry gel caused by the high alkali system. At the same time, the trace water produced by acid-base neutralization can be absorbed by the cross-linked sodium polyacrylate and fixed by its cross-linked structure, thereby improving the stability of the slurry. The volume of the cross-linked sodium polyacrylate increases after absorbing water, and it can be removed by the filter. Therefore, the above method will not introduce impurity elements into the sodium ion battery slurry, and the cross-linked sodium polyacrylate remaining in the slurry can also play a role in sodium supplementation, which helps to improve the energy density of the sodium ion battery.
[0101] In some embodiments, the positive electrode current collector may be, but is not limited to, aluminum foil.
[0102] In some embodiments, the thickness of the positive electrode active layer is 60 μm to 100 μm. For example, the thickness of the positive electrode active layer can be, but is not limited to, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, or a range consisting of any two of these values.
[0103] In some embodiments, the steps of preparing the positive electrode sheet include:
[0104] Prepare a positive electrode slurry for a sodium ion battery by using a positive electrode active material, a conductive agent, a binder and cross-linked sodium polyacrylate;
[0105] The sodium ion battery positive electrode slurry is applied to at least one side surface of the positive electrode current collector and dried to prepare a positive electrode sheet.
[0106] A fifth aspect of the present application provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, and a separator separated between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.
[0107] It can be understood that the negative electrode sheet, separator, etc. of the sodium ion battery can be commonly used in the art and are not particularly limited here.
[0108] In order to make the purpose and advantages of the present application clearer, the sodium ion battery positive electrode slurry, sodium ion battery and its effects of the present application are further described in detail in combination with specific examples. It should be understood that the specific embodiments described herein are only used to explain the present application and shall not be used to limit the present application. The following examples do not include other components except unavoidable impurities unless otherwise specified. The drugs and instruments used in the examples are conventionally selected in the art unless otherwise specified. The experimental methods for which specific conditions are not specified in the examples are implemented according to conventional conditions, such as the conditions described in the literature and books, or the methods recommended by the manufacturer.
[0109] Example 1
[0110] This embodiment provides a sodium ion battery positive electrode slurry, which includes, by weight: a layered transition metal oxide NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O264 parts, conductive agent conductive carbon black 1 part, binder PVDF Solvay 5130 2 parts, cross-linked sodium polyacrylate 0.8 parts and solvent N-methylpyrrolidone 40 parts. Among them, the cross-linked sodium polyacrylate has a neutralization degree of 50% and a particle size of 50μm~100μm. The preparation steps are as follows:
[0111] In a 5L glass reactor, add 1127g of 32% sodium hydroxide solution and 1273g of deionized water, slowly add 1300g of acrylic acid under stirring, and cool to 20°C with cooling water. Then add 1.2g of polyethylene glycol diacrylate (PEGDA, molecular weight 508), 4.2g of ethoxylated trimethylolpropane triacrylate crosslinker (TMP(EO)15TA), 5.0g of 1% diethylenetriamine pentaacetic acid pentasodium (EDTA(5Na)) aqueous solution and 21.6g of 1% sodium dodecyl sulfate aqueous solution, and mix well. Then add 26g of 1% diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide (IRGACURE 819) acrylic acid solution, 10.4g of 5% sodium persulfate aqueous solution and 13g of 1% sodium pyrosulfite aqueous solution. The obtained solution was mixed evenly and poured into a rectangular polymerization tank, and then placed in a UV irradiation device at a light intensity of 5mw / cm 2The polymerization is initiated under the light conditions, and the polymerization reaction occurs in about 30 seconds, and foaming and gel production are produced at the same time. The aging is continued for 5 minutes. Then the polymerized colloid is taken out, and the colloid is continuously added into the screw crushing granulator for gel granulation to obtain a 4mm×4mm gel block absorbent polymer lipid, which is then dried in a blast oven at 150℃ for 1h. The dried particles are crushed by a pulverizer and classified by a sieve to obtain a cross-linked sodium polyacrylate with a particle size of 50μm~100μm.
[0112] The method for preparing the positive electrode slurry for a sodium ion battery of the present embodiment comprises the following steps:
[0113] Step S1: 64 parts by mass of layered transition metal oxide NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, 1 part of conductive carbon black, 2 parts of binder PVDF Solvay 5130 and 0.8 parts of cross-linked sodium polyacrylate were mixed and stirred at a revolution rate of 20 rpm and a rotation rate of 500 rpm for 30 minutes.
[0114] Step S2: Add 40 parts of organic solvent N-methylpyrrolidone to the mixture obtained in step S1, and stir at a revolution rate of 30 rpm and a rotation rate of 2000 rpm for 180 min. The vacuum degree during stirring is ≤-90 KPa.
[0115] Step S3: Filter the slurry obtained in step S2 using a 150-mesh filter to remove large-particle-sized cross-linked sodium polyacrylate to obtain the positive electrode slurry for the sodium ion battery of this embodiment.
[0116] The viscosity of the positive electrode slurry of the sodium ion battery prepared in this embodiment is 6050 cp, and after standing for 5 hours, the viscosity is 7500 cp, and no gelation occurs. Wherein, gelation means that the viscosity of the positive electrode slurry of the sodium ion battery is greater than 20000 cp.
[0117] Example 2
[0118] The present embodiment provides a sodium ion battery positive electrode slurry, which is similar to the sodium ion battery positive electrode slurry of Example 1, except that the addition amount and neutralization degree of cross-linked sodium polyacrylate are different. In the present embodiment, the mass fraction of cross-linked sodium polyacrylate is 1.3 parts, and the neutralization degree is 70%. Specifically, the neutralization degree of cross-linked sodium polyacrylate is adjusted by adjusting the addition amount of sodium hydroxide solution with a mass percentage concentration of 32% in the preparation process of cross-linked sodium polyacrylate in Example 1. In the preparation process of the cross-linked sodium polyacrylate of the present embodiment, 1578g of sodium hydroxide solution with a mass percentage concentration of 32% and 822g of deionized water are added to prepare a cross-linked sodium polyacrylate with a neutralization degree of 70%. The other steps and parameters are the same as those in Example 1 and are not repeated here.
[0119] The viscosity of the sodium ion battery positive electrode slurry prepared in this embodiment is 6900 cp. After standing for 5 hours, the viscosity is 8200 cp, and no gelation occurs.
[0120] Example 3
[0121] The present embodiment provides a sodium ion battery positive electrode slurry, which is similar to the sodium ion battery positive electrode slurry of Example 1, except that the addition amount and neutralization degree of cross-linked sodium polyacrylate are different. In the present embodiment, the mass fraction of cross-linked sodium polyacrylate is 4.1 parts, and the neutralization degree is 90%. Specifically, the neutralization degree of cross-linked sodium polyacrylate is adjusted by adjusting the addition amount of sodium hydroxide solution with a mass percentage concentration of 32% in the preparation process of cross-linked sodium polyacrylate in Example 1. In the preparation process of the cross-linked sodium polyacrylate of the present embodiment, 2030g of sodium hydroxide solution with a mass percentage concentration of 32% and 370g of deionized water are added to prepare a cross-linked sodium polyacrylate with a neutralization degree of 90%. The other steps and parameters are the same as those in Example 1 and will not be repeated.
[0122] The viscosity of the sodium ion battery positive electrode slurry prepared in this embodiment is 7550 cp. After standing for 5 hours, the viscosity is 8500 cp, and no gelation occurs.
[0123] Example 4
[0124] The present embodiment provides a sodium ion battery positive electrode slurry, which is similar to the sodium ion battery positive electrode slurry of Example 1, except that the cross-linked sodium polyacrylate is directly commercially available, purchased from Wanhua Chemical, brand WANICE® WHS 600, with a neutralization degree of 75%, and the commercially available particles are crushed by a pulverizer and sieve-graded to obtain a cross-linked sodium polyacrylate with a particle size of 50 μm to 100 μm. In this embodiment, the mass fraction of cross-linked sodium polyacrylate is 1.35 parts. The other steps and parameters are the same as in Example 1 and will not be repeated.
[0125] The viscosity of the sodium ion battery positive electrode slurry prepared in this embodiment is 7200 cp. After standing for 5 hours, the viscosity is 8150 cp, and no gelation occurs.
[0126] Comparative Example 1
[0127] Comparative Example 1 provides a sodium ion battery positive electrode slurry, which is similar to the sodium ion battery positive electrode slurry of Example 1, except that no cross-linked sodium polyacrylate is added, and other steps and parameters are the same as those of Example 1 and will not be repeated.
[0128] The viscosity of the sodium ion battery positive electrode slurry prepared in this comparative example is 14500 cp. After standing for 5 hours, the viscosity is 22500 cp, and gelation occurs.
[0129] Comparative Example 2
[0130] Comparative Example 2 provides a sodium ion battery positive electrode slurry, which is similar to the sodium ion battery positive electrode slurry of Example 1, except that the addition amount and neutralization degree of cross-linked sodium polyacrylate are different. In this embodiment, the mass fraction of cross-linked sodium polyacrylate is 0.7 parts, and the neutralization degree is 40%. Specifically, the degree of neutralization of cross-linked sodium polyacrylate is adjusted by adjusting the addition amount of sodium hydroxide solution with a mass percentage concentration of 32% in the preparation process of cross-linked sodium polyacrylate in Example 1. In the preparation process of the cross-linked sodium polyacrylate of this embodiment, 902g of sodium hydroxide solution with a mass percentage concentration of 32% and 1498g of deionized water are added to prepare a cross-linked sodium polyacrylate with a neutralization degree of 40%. The other steps and parameters are the same as those in Example 1 and are not repeated here.
[0131] The viscosity of the sodium ion battery positive electrode slurry prepared in this comparative example is 6100 cp. After standing for 5 hours, the viscosity is 9800 cp, and no gelation occurs.
[0132] Comparative Example 3
[0133] Comparative Example 3 provides a sodium ion battery positive electrode slurry, which is similar to the sodium ion battery positive electrode slurry of Example 1, except that the addition amount and neutralization degree of cross-linked sodium polyacrylate are different. In this embodiment, the mass fraction of cross-linked sodium polyacrylate is 8.7 parts, and the neutralization degree is 95%. Specifically, the degree of neutralization of cross-linked sodium polyacrylate is adjusted by adjusting the addition amount of sodium hydroxide solution with a mass percentage concentration of 32% in the preparation process of cross-linked sodium polyacrylate in Example 1. In the preparation process of cross-linked sodium polyacrylate in this embodiment, 2142g of sodium hydroxide solution with a mass percentage concentration of 32% and 258g of deionized water are added to prepare a cross-linked sodium polyacrylate with a neutralization degree of 95%. The other steps and parameters are the same as those in Example 1 and are not repeated here.
[0134] The viscosity of the sodium ion battery positive electrode slurry prepared in this comparative example is 7600 cp. After standing for 5 hours, the viscosity is 10500 cp, and no gelation occurs.
[0135] The viscosity test method is as follows: at 25° C., 500 mL of the sodium ion positive electrode slurry obtained in the above embodiments and comparative examples is placed in a beaker and measured for 4 minutes using a viscosity meter.
[0136] After the positive electrode slurry of the sodium ion battery obtained in the above embodiments and comparative examples is coated on aluminum foil, it is dried and other steps to prepare the positive electrode sheet, and then wound with the separator and the negative electrode sheet into a roll core, wherein the separator completely covers the positive electrode sheet and the negative electrode sheet, and the obtained roll core is wrapped with an aluminum plastic film and injected with an electrolyte, and finally a sodium ion battery is made through processes such as standing, forming, and volume separation. Among them, the preparation method of the negative electrode sheet includes the following steps: hard carbon, conductive carbon black, and negative electrode binder PVDF are mixed with an appropriate amount of NMP in a mass ratio of 95:2:3 to prepare a negative electrode slurry, which is coated on a copper foil, air-dried at 100°C, and cold-pressed and cut into negative electrode sheets.
[0137] The performance of the sodium ion battery prepared by using the sodium ion battery positive electrode slurry of each embodiment and comparative example was tested, and the specific test method is as follows:
[0138] Cycle performance test: At 25°C, the sodium ion battery prepared above was charged to 4.0V at 0.5C constant current and constant voltage, with a cut-off condition of 0.05C; after standing for 60 minutes, it was discharged to 2.0V at 0.5C, and the above process was continued until the number of cycles reached 300, and the capacity retention rate was recorded.
[0139] Discharge capacity test: The battery is discharged at 0.2C constant current to 2V and allowed to stand for 10 minutes; charged at 0.2C constant current and constant voltage to 4.25V and allowed to stand for 10 minutes; discharged at 0.2C constant current to 2V and allowed to stand for 10 minutes, and the 0.2C discharge capacity is recorded to obtain the battery capacity.
[0140] The test results are shown in Table 1 below.
[0141] Table 1 Performance test results of sodium ion battery positive electrode slurry and battery of each embodiment and comparative example
[0142]
[0143] As can be seen from Table 1, by comparing Examples 1-4 with Comparative Example 1, after adding cross-linked sodium polyacrylate, the discharge viscosity of the positive electrode slurry of the sodium ion battery is significantly reduced, and the viscosity is stable after 5 hours of standing, and the 0.2C first discharge capacity and cycle capacity retention rate are improved. The reason is that the carboxylic acid group contained in the cross-linked sodium polyacrylate can effectively neutralize the residual alkali of the sodium ion positive electrode active material, thereby inhibiting the slurry gel caused by the high alkali system, and at the same time, the trace water produced by the acid-base neutralization can be absorbed and fixed in the cross-linked sodium polyacrylate, thereby improving the stability of the slurry. The cross-linked sodium polyacrylate retained in the positive electrode slurry acts as a sodium supplement, improves the energy density of the sodium ion battery, and improves the cycle performance.
[0144] In Comparative Examples 2-3, since the neutralization degree of the cross-linked sodium polyacrylate used is too low or too high, the water absorption and water retention capacity is poor, and the residual trace water causes the battery discharge capacity and cycle performance to be worse than those of Examples 1-4.
[0145] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0146] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the protection scope of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the protection scope of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A sodium ion battery positive electrode slurry, characterized in that: include: Positive electrode active material, conductive agent, binder, cross-linked sodium polyacrylate and organic solvent; Wherein, the neutralization degree of the cross-linked sodium polyacrylate is 50% to 90%.
2. The positive electrode slurry for sodium ion battery according to claim 1, characterized in that: The neutralization degree of the cross-linked sodium polyacrylate is 55% to 75%.
3. The sodium ion battery positive electrode slurry according to claim 1 or 2, characterized in that: The average particle size of the cross-linked sodium polyacrylate is 10 μm to 400 μm, and optionally, the average particle size is 50 μm to 200 μm.
4. The positive electrode slurry for sodium ion battery according to claim 1 or 2, characterized in that: Calculated by weight, the raw materials of the sodium ion battery positive electrode slurry include: 45 to 65 parts of positive electrode active material, 0.5 to 2.5 parts of conductive agent, 1.2 to 3.5 parts of binder, 0.5 to 4.5 parts of cross-linked sodium polyacrylate and 20 to 45 parts of organic solvent.
5. The positive electrode slurry for sodium ion battery according to claim 4, characterized in that: One or more of the following conditions are met: (1) The positive electrode active material comprises one or a combination of layered transition metal oxides, Prussian blue-based positive electrode materials and polyanion compounds; (2) The binder includes one or a combination of polyvinylidene fluoride, polyacrylic acid and polytetrafluoroethylene; Optionally, the binder includes polyvinylidene fluoride; (3) The conductive agent includes one or a combination of carbon nanotubes, conductive carbon black and graphene; (4) The solvent includes one or a combination of N-methylpyrrolidone and N,N-dimethylformamide.
6. The positive electrode slurry for sodium ion battery according to claim 1, 2 or 5, characterized in that: The raw materials for preparing the cross-linked sodium polyacrylate include: acrylic acid, a cross-linking agent, a neutralizing agent and an initiator; Wherein, the crosslinking agent includes one or more of N,N-methylenebisacrylamide, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diacrylate, polyethylene glycol diglycidyl ether, ethoxylated glycerol triacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, allyl methacrylate, triallylamine, tetraallyl ammonium chloride, tetraallyloxyethane, pentaerythritol triacrylate, pentaerythritol triallyl ether, trimethylolpropane triacrylate and ethoxylated trimethylolpropane triacrylate; The neutralizing agent includes one or more of alkali metal hydroxides, alkali metal oxides, alkali metal carbonates, alkali metal bicarbonates and ammonium salts. Optionally, the neutralizing agent includes one or more of sodium hydroxide, sodium carbonate and sodium bicarbonate. The initiator includes one or more of an oxidant, a reducing agent and a photoinitiator; The oxidant includes one or more of hydrogen peroxide, sodium persulfate, potassium persulfate, ammonium persulfate, tert-butyl hydroperoxide, di-tert-butyl peroxide and azo compounds. Optionally, the oxidant includes one or more of azobisisobutyronitrile, azobisdimethylvaleronitrile, 2,2-azobis(2-amidinopropane) dihydrochloride, azobisamidinopropane dihydrochloride, 2,2-azobis(N,N-dimethyleneisobutyramidine) dihydrochloride, 2-(carbamoylazo)isobutyronitrile and 4,4'-azobis(4-cyanovaleric acid); The reducing agent includes one or more of ascorbic acid, ammonium bisulfite, sodium sulfite, sodium bisulfite, sodium pyrosulfite, sodium thiosulfate, ammonium thiosulfate, ammonium dithionite, ammonium sulfide, alkali metal bisulfite, alkali metal sulfate, alkali metal thiosulfate, alkali metal dithionite and alkali metal sulfide; optionally, the reducing agent includes one or more of ascorbic acid, sodium sulfite and sodium pyrosulfite; The photoinitiator includes one or more of benzophenone, benzoin ether, dialkyl acetophenone, hydroxyalkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and α-amino ketone.
7. A method for preparing sodium ion battery slurry, characterized in that: The steps include: The positive electrode active material, the conductive agent, the binder, the cross-linked sodium polyacrylate and the organic solvent are mixed and stirred, and then filtered to prepare a positive electrode slurry for a sodium ion battery; Wherein, the neutralization degree of the cross-linked sodium polyacrylate is 50% to 90%; Optionally, the step of mixing and stirring the positive electrode active material, the conductive agent, the binder, the cross-linked sodium polyacrylate and the organic solvent comprises: Mixing and stirring the positive electrode active material, the conductive agent, the binder and the cross-linked sodium polyacrylate for the first time; The organic solvent is added to the obtained mixture, and mixing and stirring are performed for the second time.
8. Application of cross-linked sodium polyacrylate in preparing positive electrode slurry for sodium ion battery, characterized in that: The neutralization degree of the cross-linked sodium polyacrylate is 50% to 90%; Optionally, the neutralization degree of the cross-linked sodium polyacrylate is 55% to 75%; and / or, The average particle size of the cross-linked sodium polyacrylate is 10 μm to 400 μm, and optionally, the average particle size is 50 μm to 200 μm.
9. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active layer arranged on at least one side of the positive electrode current collector, wherein the positive electrode active layer is prepared by the positive electrode slurry of a sodium ion battery according to any one of claims 1 to 6 or the positive electrode slurry of a sodium ion battery prepared by the preparation method according to claim 7.
10. A sodium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet is as described in claim 9.